Organic Mulching Effects on Water Productivity, Soil Temperature, Growth and Yield of Lentil Varieties - Shirisha, Karupakula; Ray, Lala I. P.; Parida, Pradosh Kumar; Singh, A. K.; Singh, N. J. (International Journal of Bio-resource and Stress Management, 2023)
The experiment was conducted at College of Post Graduate Studies in Agricultural Sciences, Umiam, Meghalaya during the rabi season (November–April, 2022) to study the effect of organic mulching on growth, yield and water productivity of lentil varieties in mid-hills of Meghalaya. The experiment was carried out in split plot design with four mulch treatment under main plot (M0: un-mulch/control, M1: paddy straw mulch, M2: maize stover mulch, M3: weed mulch) and four varietal treatments under sub plot (V1: HUL-57, V2: PL-4, V3: PDL-1 and V4: PSL-9) which were replicated thrice. Results indicated that, plant height, number of branches plant-1, water productivity were highest under paddy straw mulch. Paddy straw mulch (43.57) which was on par with weed mulch (41.29) has reported significantly highest number of pods plant-1 over maize stover mulch (38.18) and un-mulch (36.21) treatments. Different mulches have reported economic yield advantage of 21.01% to 10.55% over the control. Water productivity has found significantly higher under paddy straw mulch (3.25 kg ha-1 mm-1) over the control treatment (2.57 kg ha-1 mm-1). Mulches also modified soil thermal regimes and effected plant growth and development. Soil temperature has shown increasing trend towards the end of crop season, since, air temperatures are increasing towards the end of growing season. Paddy straw mulch, weed mulch and maize stover mulch increased 2.31oC, 1.88oC, 0.27oC temperature, respectively, over the control during morning hours.